Structural organization of ionic liquids embedded in fluorinated polymers - Petrenko, Viktor I. (2022)
Hybrid materials based on ionic liquids (ILs) and polymers are increasingly being used for the development of smart and multifunctional materials, allowing to tune polymer properties or introduce new ones. Nonetheless, the structural organization of ILs within the polymer matrix is not properly understood. This work reports on the structural organization of different ILs incorporated into polyvinylidene fluoride (PVDF) films. The effect of IL type ([Pmim][TFSI], [Pmpip][TFSI], [Bmim]2[NiCl4] and [Bmim][FeCl4) incorporated into the PVDF matrix on the structural organization was evaluated and correlated to the observed variations in the morphological and physical-chemical properties. [Bmim][FeCl4] and [Bmim]2[NiCl4] leads to highly porous structures and the incorporation of ILs into the polymer matrix increases the electroactive β phase content of PVDF. Different structural organization of the hybrid materials at nanoscale has been found by small-angle neutron scattering experiments. Whereas just single polydisperse objects with average size of about 5 nm have been found in PVDF/[Pmim][TFSI] and PVDF/[Pmpip][TFSI] samples, more complex fractal-like organization of pores are present in PVDF/[Bmim][FeCl4] and PVDF/[Bmim]2[NiCl4]. Thus, IL type influences both the morphology and the electroactive phase of the polymer. Complex fractal-like organization observed for [Bmim][FeCl4] and [Bmim]2[NiCl4] into the PVDF matrix allows a porous morphology, while single polydispersed particles of [Pmpip][TFSI] or [Pmpip][TFSI] into PVDF favors strong ion-dipole interactions between the IL and the polymer matrix, resulting in higher electroactive β phase contents.